2022
DOI: 10.1007/s40123-022-00489-9
|View full text |Cite
|
Sign up to set email alerts
|

Biometric Determinants of Epithelial Thickness Profile Across a Wide Range of Refractive Errors

Abstract: Introduction: To evaluate the corneal epithelial thickness (CET) profiles and their correlations with axial length (AL) and anterior corneal radius of curvature (Rm F) across different refractive error groups. Methods: A total of 1225 eyes of 616 normal patients were included. CET mapping, AL, and Rm F were obtained using spectral-domain optical coherence tomography, optical biometry, and Scheimpflug corneal tomography, respectively. In the CET map, one central (2 mm), eight paracentral (2-5 mm), and eight per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
5
1
3
Order By: Relevance
“…Although a potential variable that could affect CET is refractive status, no reports of a correlation between refractive defect and CET have been reported yet. 6,21 Although Ozalp et al 22 reported thinning in corneal epithelial thickness in all quadrants, it was statistically significant only in the superior and superonasal quadrants at the 2-5 mm and 5-6 mm-diameter rings but not in the central 2 mm area that was the area of interest in our study.…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…Although a potential variable that could affect CET is refractive status, no reports of a correlation between refractive defect and CET have been reported yet. 6,21 Although Ozalp et al 22 reported thinning in corneal epithelial thickness in all quadrants, it was statistically significant only in the superior and superonasal quadrants at the 2-5 mm and 5-6 mm-diameter rings but not in the central 2 mm area that was the area of interest in our study.…”
contrasting
confidence: 64%
“…It would be interesting to have more studies investigating the central as well as the more peripheral epithelial thickness since some studies revealed prominent thinning of the mid-peripheral CET with age. 1 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…Клінічні симптоми ССО, такі як подразнення очей, фотосенсибілізація та флюктуація зору, на нашу думку й за даними літератури, можуть бути ознакою пошкодження епітелію рогівки [17]. На ОСТ і кератотопограмі ми фіксували морфологічні зміни, які підтверджували пошкодження поверхневого шару рогівки при персистуючому ССО.…”
Section: обговоренняunclassified
“…Що стосується оптичної когерентної томографіїбезконтактного методу, що досить важливо після ЕЛК, то він дає змогу точно визначити товщину епітелію рогівки (CET) завдяки високій аксіальній роздільній здатності. [17]. Попередні дослідження повідомляли про хорошу повторюваність вимірювань товщини рогівки й епітелію за допомогою систем візуалізації ОСТ [18,19].…”
Section: обговоренняunclassified
See 1 more Smart Citation